Revendo os códigos hamming e CRC para tratar com erros na transmissão de dados - Lopes, Deisy Piedade Munhoz [UNESP] (My University, 2003)
This article has the purpose to review the main codes used to detect and correct errors in data communication specifically in the computer's network. The Hamming's code and the Ciclic Redundancy Code (CRC) are presented as the focus of this article as well as CRC hardware implementation. Each code is reviewed in details in order to fill the gaps in the literature and to make it accessible to the computer science and engineering students as well as to anyone who may be interested in learning the technique to treat error in data communication.
Review of the hamming and CRC codes to handle errors in data transmission
Keywords: Data transmission; Errors codes; Hamming code; Polynomials codes; Codes (symbols); Computer networks; Computer science; Data communication systems; Engineering; Error detection; Learning systems; Students; Error codes; Data transfer